Industry views of the UK Soft Drinks Industry Levy: a thematic analysis of elite interviews with food and drink industry professionals, 2018–2020 - Jean Adams; Martin White; Harry Rutter; Richard Smith; Steven Cummins; Tarra L Penney; Hannah Forde; Cherry Law; Catrin P Jones; Dolly van Tulleken (BMJ Open)
Objectives The UK Soft Drinks Industry Levy (SDIL), implemented in 2018, has been successful in reducing the sugar content and purchasing of soft drinks, with limited financial impact on industry. Understanding the views of food and drink industry professionals involved in reacting to the SDIL is important for policymaking. However, their perceptions of the challenges of implementation and strategic responses are unknown. The aim of this study, therefore, was to explore how senior food and drink industry professionals viewed the SDIL.Design We undertook a qualitative descriptive study using elite interviews. Data were analysed using Braun and Clarke’s thematic analysis, taking an inductive exploratory and descriptive approach not informed by prior theory or frameworks.Setting and participants Interviews were conducted via telephone with 14 senior professionals working in the food and drink industry.Results Five main themes were identified: (1) a level playing field…for some; industry accepted the SDIL as an attempt to create a level playing field but due to the exclusion of milk-based drinks, this was viewed as inadequate, (2) complex to implement, but no lasting negative effects; the SDIL was complex, expensive and time consuming to implement, with industry responses dependent on leadership buy-in, (3) why us?—the SDIL unfairly targets the drinks industry; soft drinks are an unfair target when other categories also contain high sugar, (4) the consumer is king; consumers were a key focus of the industry response to this policy and (5) the future of the SDIL; there appeared to be a wider ripple effect, which primed industry to prepare for future regulation in support of health and environmental sustainability.Conclusions Insights from senior food and drink industry professionals illustrate how sugar-sweetened beverage taxes might be successfully implemented and improve understanding of industry responses to taxes and other food and drink policies.Trial registration number ISRCTN18042742.